1993
DOI: 10.1080/00268979300102281
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of CO2over univalent cation-exchanged ZSM-5 zeolites

Abstract: Isotherms and IR spectra were measured for CO2-MZSM-5 (M = Li +, Na +, K +, Rb +, Cs +) adsorption systems. The observed adsorption characteristics were well approximated by a physical adsorption where the van der Waals force and an electrostatic interaction force are operating: the degree of irreversible adsorption (chemisorption) was less than 10% of the total adsorption. Although the adsorbed CO2 molecule interacts with both the cation and the pore wall, only the CO2-cation interaction can convert the IR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 30 publications
8
59
1
Order By: Relevance
“…Hence, the zeolites such as ZSM-5 and M-ZSM-5 (M = Li + , Na + , K + , Rb + , Cs + ) which have small cations might penetrate more easily within channels, are able to interact more strongly with the CO 2 [19,33]. This is in agreement with the results from a study performed by Yamazaki et al [21]. They showed that energy of the interaction between the CO 2 and the cations sites of zeolites M-ZSM-5 (M = Li + , Na + , K + , Rb + , Cs + ) decreases with the increase of the size of these cations sites.…”
Section: Influence Of the Polarizing Power Distribution Size And Nusupporting
confidence: 83%
See 3 more Smart Citations
“…Hence, the zeolites such as ZSM-5 and M-ZSM-5 (M = Li + , Na + , K + , Rb + , Cs + ) which have small cations might penetrate more easily within channels, are able to interact more strongly with the CO 2 [19,33]. This is in agreement with the results from a study performed by Yamazaki et al [21]. They showed that energy of the interaction between the CO 2 and the cations sites of zeolites M-ZSM-5 (M = Li + , Na + , K + , Rb + , Cs + ) decreases with the increase of the size of these cations sites.…”
Section: Influence Of the Polarizing Power Distribution Size And Nusupporting
confidence: 83%
“…Zeolites have a high potential for CO 2 capture, reaching an adsorption efficiency of 5.5 mmol of CO 2 /g of zeolite, combined with a degree of irreversible adsorption inferior to 10% (tables 1-3) [9][10][11][12][13][14][15][16][17][18][19][20][21]. The CO 2 adsorption is influenced by diverse structural characteristics of zeolites including size, polarizing power, distribution and the number of exchangeable cations in their cavities, the size of the pores and the Si/Al ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The new CO 2 -zeolite interaction mixed the CLAYFF zeolite with CLAYFF parameters for the oxygen of CO 2 and EPM2 with a slightly modified r (Lennard-Jones size parameter) value for C. Figure 11 shows isotherms for CO 2 in silicalite (MFI) using this modified potential, which can be seen to reproduce the experimental isotherms of Yamazaki et al [54] very well. Using these isotherms, we calculate the heat of adsorption to be 17 kJ/mol which is slightly lower than the value published by Yamazaki et al of 23.4 kJ/mol; however, their calculation was over the temperature range 273-473 K, while our calculation was between 263 and 283 K, which may account for the different values.…”
Section: Development Of Modelsupporting
confidence: 62%